Relationship between Academic Stress and Personal Wellness in Medical University Students: LMRJ - Yousuf, Tahira (LIAQUAT MEDICAL RESEARCH JOURNAL, 2019)
To explore the relationship of academic stress with personal wellness as well as academic stress as a predictor of personal wellness in medical university students. One seventy ve under graduate students, i.e. sixty seven males and one hundred and eight females were selected through convenient sampling for the present study. is study was conducted during February 2017 to July 2017 at Jinnah Medical & Dental College (JMDC) and Bahria University Medical & Dental College (BUMDC). Participants were assessed by using Lakaev Academic Stress Response Scale (Lakaev, 2009) and Five Factor Wellness Inventory Adult Form (Witmer & Sweeney, 2004). e results found a signicant relationship between personal wellness in medical university students (p ? .001). e ndings indicated a moderate downhill (negative) relationship between academic stress and personal wellness as per the hypotheses statement. A slight deviation from the results has occurred which might be due to some extraneous variable.